Spatial distribution of economic entities and their classification according to technology levels in the Dolnośląskie voivodship. - Raczyk, Andrzej; Dobrowolska-Kaniewska, Helena (Bulletin of Geography. Socio-economic Series, 2007)
Contemporary socio-economic processes increase the significance of domains which rely heavily on intensive knowledge utilization. It concerns, above all, the II and III sector of the economy. The purpose of this study was to examine the shaping of spatial diversity of economic entities in the industry sector measured by technology levels and the service sector assessed by intensity of research and development at the local level. The analysis also concerned factors determining the creation of these diversities as well as relationships between the occurrence of economic entities in production activity and the service sector. The survey was conducted at the level of NTS 4 units (counties) in the Dolnośląskie Voivodeship in 1998 and 2004. The analysis revealed an increase in the participation of entities belonging to the high tech service sector and high tech industry sector at the local level of the Dolnośląskie Voivodeship. This participation was accompanied by a tendency of their spatial structures to become alike. It indicates that general conditions of emergence of companies characterized by the highest level of research and development intensity within the II and III sector of the economy are becoming alike. The development of high tech industry companies is connected with the general development of services. This interrelation increases together with intensity of research and development within sector III (high tech services and knowledge-based services). It also increases with time. There exists a high, positive correlation between the value of the entrepreneurship index in the II and III sector and the general level of entrepreneurship. The crucial factor determining the formation of new economic entities in the group of high tech industry companies and high tech services is the overall rise of entrepreneurship index.